2018
DOI: 10.1016/j.conbuildmat.2017.12.233
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of fungi with concrete: Significant importance for bio-based self-healing concrete

Abstract: The goal of this study is to explore a new self-healing concept in which fungi are used as a self-healing agent to promote calcium mineral precipitation to fill the cracks in concrete. An initial screening of different species of fungi has been conducted. Fungal growth medium was overlaid onto cured concrete plate. Mycelial discs were aseptically deposited at the plate center. The results showed that, due to the dissolving of Ca(OH)2 from concrete, the pH of the growth medium increased from its original value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(86 citation statements)
references
References 83 publications
1
84
0
1
Order By: Relevance
“…The processes of calcite biomineralization are much more complex, since they are related to the special features of fungi metabolism and the mechanisms of their adaptation to the existence in high-alkaline environment [36][37][38]. The fungi from Penicillium group secrete various organic acids, including oxalic acid that shifts the pH of the medium to the acidic values and inhibits the crystallization of calcite and promote the crystallization of oxalates [39][40][41]. Electron microscopy showed that precipitation of CaCO 3 by fungi has two ways: spherocrystals with a fibrous structure and hyphal mineralization (biomorphosis).…”
Section: Discussionmentioning
confidence: 99%
“…The processes of calcite biomineralization are much more complex, since they are related to the special features of fungi metabolism and the mechanisms of their adaptation to the existence in high-alkaline environment [36][37][38]. The fungi from Penicillium group secrete various organic acids, including oxalic acid that shifts the pH of the medium to the acidic values and inhibits the crystallization of calcite and promote the crystallization of oxalates [39][40][41]. Electron microscopy showed that precipitation of CaCO 3 by fungi has two ways: spherocrystals with a fibrous structure and hyphal mineralization (biomorphosis).…”
Section: Discussionmentioning
confidence: 99%
“…These methods contemplate approximately 90 species considered common and important indoors (Adams et al, 2013). Luo et al (2018) emphasize the needed to evaluate how coatings and surface treatment can affect the fungi growth and survivor.…”
Section: IVmentioning
confidence: 99%
“…They are sources of spores that can cause allergic reaction or asthma to sensitive people [13]. According to the results presented by Luo et al [14], due to dissolving of Ca(OH) 2 from cement materials by moulds, the pH of the growth medium can increase from the original value of 6.5 up to 13.0. It is possible that moulds as the algae and bacteria (they were not studied in the present study but their presence can be expected) were participating on calcium solution in lime building materials.…”
Section: Mouldsmentioning
confidence: 99%